2023
DOI: 10.1108/mip-03-2023-0097
|View full text |Cite
|
Sign up to set email alerts
|

Do extrinsic factors encourage shoppers’ compulsive buying? Store environment and product characteristics

Abstract: PurposeThe study examines the extrinsic variables, namely store environment, promotional activities (PA), product features and stimulation factors that encourage compulsive purchasing in emerging markets.Design/methodology/approachThe data were collected from customers with recent compulsive shopping experiences at an online retail store. This study collected 469 original survey responses employing purposive sampling and data analyzed with covariance-based structural equation modeling and used segmentation ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The genesis of compulsive buying behavior is linked to external factors like pricing, product promotion, and credit cards (Workman & Paper, 2010). Recent research also takes a detailed look at external factors (Nanda, Banerji, & Singh, 2023;Lavuri & Thaichon, 2023). Although both factors can individually lead to the emergence of shopping disorders, in most cases it is their mutual interaction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The genesis of compulsive buying behavior is linked to external factors like pricing, product promotion, and credit cards (Workman & Paper, 2010). Recent research also takes a detailed look at external factors (Nanda, Banerji, & Singh, 2023;Lavuri & Thaichon, 2023). Although both factors can individually lead to the emergence of shopping disorders, in most cases it is their mutual interaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previously, Kaur, Maheshwari, and Kumar (2019) recommended that marketers think about using different markup techniques for different visible places. In general, the external elements found in the store setting and the attributes of the products can be quite influential in promoting consumers' compulsive buying behavior (Lavuri & Thaichon, 2023). However, it is crucial to recognize that excessive shopping can also have negative effects through the process of negative reinforcement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, existing studies found that retail price promotion positively affects store sales [34][35][36][37]. In particular, an increasing number of retailers use free shipping to promote sales [10,17,19,20,23].…”
Section: Promotion Strategy and Consumers' Purchase Decisionsmentioning
confidence: 99%